Ultra-compact terahertz 50:50 power splitter designed by a perceptron-based algorithm - Kim, Sunwook; Kim, Nanhee; Park, Ikmo; Han, Haewook (Optics Continuum, 2022)
We designed and simulated an ultra-compact 1 × 2 power splitter operating in the terahertz region. A machine learning approach was implemented to design the photonic device. The designed power splitter has a footprint of 500 µm × 500 µm. We calculated the insertion loss using a three-dimensional finite difference time domain method. The calculated insertion loss was less than 4 dB over the operating wavelength range of 275–325 µm. The machine learning algorithm implemented in this work can be applied to the inverse design of various photonic devices.
Keywords: Inverse designs; Machine learning algorithms; Machine learning approaches; Operating wavelength; Photonics devices; Power splitters; Tera Hertz; Terahertz region; Three dimensional finite difference time domain methods; Wavelength ranges